Identification of Potential Key Agents for Targeting RNA-Dependent RNA Polymerase of SARS-CoV-2 by Integrated Analysis and Virtual Drug Screening - Ao, Shuang; Han, Dan; Sun, Lei; Wu, Yanhong; Liu, Shuang; Huang, Yaojiang (Frontiers in Genetics, 2020)
BBackground RNA-dependent RNA polymerase (RdRp) is the key enzyme responsible for the SARS-CoV-2 replication process and catalyzes the synthesis of complementary minus strand RNA and genomic plus strand RNA, often recognized as good targets for antiviral drugs. Methods A systematic screening of existing antiviral compounds, family analysis, conserved domain analysis, three-dimensional structure modeling, drug virtual screening, and bioassays were performed to identify agents that potentially targeted RNA-dependent RNA polymerase of SARS-CoV-2. Results Four thousand nine hundred and forty seven antiviral lead compounds were selected and evaluated by systematic screening. Of these, 359 agents were screened by family analysis and conserved domain analysis. They were further analyzed by three-dimensional structure modeling, virtual drug screening, and bioassays. The results identified 102 agents with potential for repurposing to target the RNA-dependent RNA polymerase of SARS-CoV-2. Conclusions This study identified 102 key agents with potential anti-SARS-CoV-2 RNA-dependent RNA polymerase function and prospects of rapid clinical application for the treatment of COVID-19.